Between Limb Muscle Co-activation Patterns in the Paretic Arm During Non-paretic Arm Tasks in Hemiparetic Cerebral Palsy - Hill, Nayo M.; Sukal-Moulton, Theresa; Dewald, Julius P. A. (Frontiers in Neuroscience, 2021)
Tasks of daily life require the independent use of the arms and hands. Individuals with hemiparetic cerebral palsy (HCP) often experience difficulty with fine motor tasks demonstrating mirrored movements between the arms. In this study, bilateral muscle activations were quantified during single arm isometric maximum efforts and submaximal reaching tasks. The magnitude and direction of mirrored activation was examined in 14 individuals with HCP and 9 age-matched controls. Participants generated maximum voluntary torques in five different directions and completed ballistic reaches while producing up to 80% of shoulder abduction maximum voluntary torque. EMG signals were recorded from six upper extremity muscles bilaterally. Participants with HCP demonstrated more mirrored activation when volitionally contracting the non-paretic arm than the paretic arm (F = 83.543, p < 0.001) in isometric efforts. Increased EMG activation during reach acceleration resulted in a larger increase in rest arm co-activation when reaching with the non-paretic arm compared to the paretic arm in the HCP group (t = 8.425, p < 0.001). Mirrored activation is more pronounced when driving the non-paretic arm and scales with effort level. This directionality of mirroring is indicative of the use of ipsilaterally terminating projections of the corticospinal tract originating in the non-lesioned hemisphere. Peripheral measures of muscle activation provide insight into the descending pathways available for control of the upper extremity after early unilateral brain injury.